Solid electrolyte membrane, preparation method thereof and solid-state battery

By covering the metal organic framework material on the surface of the oxide solid electrolyte and recombining it with the polymer solid electrolyte, the problem of poor pores and interface stability in the surface of the oxide electrolyte in the solid battery is solved, and the ionic conductivity of the electrolyte and the cycling performance of the battery is improved. , achieving high capacity retention rate.

CN119181844APending Publication Date: 2024-12-24中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411219946.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In existing solid-state batteries, the pores on the surface of oxide solid electrolytes lead to low ion conductivity and poor contact ability with the electrode interface, resulting in an increase in interface impedance during the cycle, affecting the stability and performance of the battery.

Method used

The surface of the oxide solid electrolyte is coated with a metal organic framework material with a highly ordered network structure, forming a metal organic framework cladding layer, and recombining it with the polymer solid electrolyte to form a composite inorganic solid electrolyte, and improving the ionic conductivity of the electrolyte.

Benefits of technology

Through the formation of the cladding layer, the ionic conductivity, stability and battery cycling performance of the electrolyte are improved. The capacity retention rate of the assembled all-solid state battery reaches more than 95% after 60 cycles after circulating at 60°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181844A_ABST
    Figure CN119181844A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a solid electrolyte membrane, a preparation method thereof and a solid-state battery. The solid electrolyte membrane comprises a composite inorganic solid electrolyte, a polymer solid electrolyte and sodium salt; the composite inorganic solid electrolyte comprises an oxide solid electrolyte and a metal organic framework coating layer coating the surface of the oxide solid electrolyte. According to the technical scheme, the surface of the oxide solid electrolyte is coated with a flexible metal organic framework material (MOFs) with a highly ordered network structure and a deformable framework to form a metal organic framework coating layer; the reduction of the electrochemical performance of the oxide solid electrolyte due to change of the microstructure of the oxide solid electrolyte or addition of other components can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a solid electrolyte membrane and a preparation method thereof, and a solid-state battery. Background Art

[0002] All-solid-state batteries use solid electrolytes that are not easy to burn or explode to replace liquid electrolytes, thereby improving the safety of the battery. Solid electrolytes are the core components of all-solid-state batteries. Solid electrolytes can be divided into organic solid electrolytes and inorganic solid electrolytes. Organic solid electrolytes are usually composed of polymer solid electrolytes, and inorganic solid electrolytes are divided into three types: oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes. Organic solid electrolytes are usually highly polar and easy to crystallize, resulting in extremely low room temperature ionic conductivity, and the electrolyte is easily oxidized and decomposed under high pressure. Therefore, pure polymer solid electrolytes are difficult to apply to all-solid-state batteries. Inorganic solid electrolytes usually exist in the form of particles or ceramic sheets, and their room temperature ionic conductivity is high, but due to their poor toughness, the way to assemble the battery is a solid mold battery, and there are challenges in applying it to soft-pack batteries. Polymer solid electrolytes and inorganic solid electrolytes have their own advantages and disadvantages. Therefore, in recent years, researchers have been committed to adding inorganic solid electrolytes as inorganic fillers to polymer solid electrolytes to form organic-inorganic composite solid electrolytes to achieve the synergistic effect of different materials, which is an effective measure to solve the technical problems of solid electrolytes.

[0003] PVDF-based polymer solid electrolytes have good mechanical strength and thermal stability, and can be matched with high-voltage positive electrodes and sodium metal negative electrodes to build high-energy-density solid-state batteries. However, there are a large number of pores on the surface of PVDF-based polymer solid electrolytes, which makes it difficult to migrate free Na through the movement of chain segments. + However, the oxide solid electrolyte has poor contact ability with the electrode interface and poor interface stability during the cycle, which leads to a rapid increase in interface impedance during the cycle. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a solid electrolyte membrane and a preparation method thereof and a solid-state battery.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A solid electrolyte membrane comprises a composite inorganic solid electrolyte, a polymer solid electrolyte and a sodium salt; the composite inorganic solid electrolyte comprises an oxide solid electrolyte and a metal organic skeleton coating layer coated on the surface of the oxide solid electrolyte.

[0007] The oxide solid electrolyte is Na3Zr2Si2PO 12、Na-β"-Al2O3、NaZr2P3O 12 、Na2Zr2S iP2O 12 、Na4Zr2Si3O 12 The constituent material of the metal organic framework coating layer is one of ZI F-8, 1,4-dicarboxyphenyl zirconium, and MI L-101 (Cr).

[0008] The composite inorganic solid electrolyte is prepared by the following method: the constituent material of the metal organic framework coating layer is mixed with the oxide solid electrolyte and then ball milled;

[0009] Preferably, the mass ratio of the constituent material of the metal organic framework coating layer to the oxide solid electrolyte is (1-5):20;

[0010] Preferably, the ball milling time is 1-10 h, preferably 5 h; the ball milling speed is 400-600 rpm / min, preferably 500 rpm / min.

[0011] The particle size of the oxide solid electrolyte is 0.5-5 μm, preferably 2 μm; the thickness of the metal organic framework coating layer is 50-800 nm, preferably 300-600 nm, more preferably 400-450 nm.

[0012] The polymer solid electrolyte is (polyvinylidene fluoride-hexafluoropropylene) copolymer PVDF-HFP; the sodium salt is one of sodium perchlorate and bis(sodium trifluorosulfonimide).

[0013] The solid electrolyte membrane has a thickness of 50-100 μm, preferably 50 μm.

[0014] The mass ratio of the composite inorganic solid electrolyte, the polymer solid electrolyte and the sodium salt is (1-10):(1-10):1; preferably 3-6):(3-5):1.

[0015] The present invention also includes a method for preparing the solid electrolyte membrane, comprising the following steps: first, adding a polymer solid electrolyte into a solvent and stirring it, adding a sodium salt and a composite inorganic solid electrolyte, and vigorously stirring to obtain a well-dispersed suspension; pouring it into a mold to form a film to obtain a solid electrolyte membrane; preferably, the solvent is one of N,N-dimethylacetamide (DMAC), acetone, and dimethylformamide (DMF) or a mixture thereof.

[0016] The present invention also includes a solid-state battery, including a positive electrode sheet, a negative electrode sheet and the solid electrolyte membrane. The positive electrode sheet uses Na3V2(PO4) as the positive electrode active material; preferably, the positive electrode sheet is prepared by the following method: Na3V2(PO4), PVDF, Super P and NaClO4 are mixed in proportion in N-methylpyrrolidone, and the obtained composite positive electrode slurry is scraped on aluminum foil and dried. Preferably, the mass ratio of Na3V2(PO4), PVDF, Super P and NaClO4 is 70:18:10:2.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The technical solution of the present invention forms a metal organic framework coating layer by coating a flexible metal organic framework material (MOFs) with a highly ordered network structure and a deformable skeleton on the surface of the oxide solid electrolyte, which can avoid the degradation of its electrochemical performance due to changing the microstructure of the oxide solid electrolyte or adding other components, forming a composite inorganic solid electrolyte, which is then composited with a polymer solid electrolyte to improve the ionic conductivity of the electrolyte. The all-solid-state sodium metal battery assembled with it as a solid electrolyte membrane can be stably cycled, and the all-solid-state battery assembled at 60°C with an electrolyte membrane having the best ionic conductivity has a capacity retention rate of more than 95% after 60 cycles, which has a good capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cycle test diagram of a solid-state battery containing a solid electrolyte membrane according to an embodiment of the present invention. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0021] Example 1

[0022] The preparation method of the composite inorganic solid electrolyte is a wet grinding method; specifically, the constituent material of the metal organic framework coating layer and the oxide solid electrolyte are mixed and then ball milled to obtain the composite inorganic solid electrolyte; the constituent material of the metal organic framework coating layer is one of ZIF-8, 1,4-dicarboxyphenylzirconium (UiO-66), and MIL-101 (Cr); and the oxide solid electrolyte is Na3Zr2Si2PO 12 (NZSP), Na-β"-Al2O3, NaZr2P3O 12 、Na2Zr2S i P2O 12 、Na4Zr2Si3O 12One of the following; the particle size is 0.5-5 μm, and 2 μm is used as an example in this application

[0023] Taking ZI F-8 coated NZSP as an example, the specific steps include: mixing ZI F-8 and NZSP (particle size 2μm) in a mass ratio of x:20 to obtain a mixture, adding zirconium oxide balls and the mixture in a mass ratio of 45:1 into a ball mill, and then dropping 2mL of anhydrous acetonitrile for ball milling. Among them, x is 1-5; the ball milling time is 5h, and the ball milling speed is 500rpm / min. Finally, the mixture is dried to obtain a composite inorganic solid electrolyte, which is recorded as xZ I F-8@NZSP;

[0024] The coating method of U iO-66 and MIL-101(Cr) on NZSP is the same as the above coating method, and specifically 3-U iO-66@NZSP and 3-MIL-101(Cr)@NZSP can be obtained.

[0025] The mass ratio of the constituent materials of the metal organic framework coating layer to the oxide solid electrolyte can be adjusted as needed, specifically 1:20, 2:20, 3:20, 4:20, 5:20, etc.; the thickness of the metal organic framework coating layer obtained after adjustment is 50-800nm, specifically 150nm, 300nm, 400nm, 420nm, 450nm, 600nm, 750nm, as shown in Table 1.

[0026] Embodiment 2:

[0027] The preparation method of polymer solid electrolyte and sodium salt comprises the following steps: first, adding polymer solid electrolyte into solvent and stirring, adding sodium salt and composite inorganic solid electrolyte, stirring vigorously to obtain a well-dispersed suspension; pouring into a mold to form a film to obtain a solid electrolyte membrane; preferably, the solvent is one or a mixture of DMF, DMAC or acetone.

[0028] The mass ratio of the composite inorganic solid electrolyte, the polymer solid electrolyte and the sodium salt is: (1-10): (1-10): 1); specifically it can be 1:1:1, 10:1:1, 5:3:1, 3:3:1, 6:3:1, 3:5:1, 6:5:1 and the like; preferably (3-6): (3-5): 1; the specific embodiments are described below.

[0029] The prepared composite inorganic solid electrolyte ZI F-8@NZSP is mixed with a polymer solid electrolyte and a sodium salt to prepare a solid electrolyte membrane, which specifically includes the following steps:

[0030] First, DMAC and acetone are mixed in a volume ratio of 1:2, and then PVDF-HFP and NaClO4 are added to the mixture of DMAC and acetone in a mass ratio of 3:1; the weight ratio of PVDF-HFP and NaClO4 in the mixture is 15wt%, and then a uniform mixture is obtained by strong stirring at room temperature for 8h, and then 1-ZIF-8@NZSP is added to the prepared solvent mixture, and the weight ratio of 1-ZIF-8@NZSP to the solvent mixture is 1:5; and a uniform mixture slurry is obtained by strong stirring at room temperature for 5h. The obtained slurry is cast in a polytetrafluoroethylene mold, placed in a 60° oven for drying for 12h, and finally a composite solid electrolyte membrane is obtained. The membrane thickness is 50-100μm, and a 50μm composite solid electrolyte membrane is preferred in the experiment.

[0031] Embodiment 3-6

[0032] The implementation method is the same as that of Example 1, except that 1-ZI F-8@NZSP needs to be replaced with 2-ZI F-8@NZSP, 3-ZI F-8@NZSP, 4-ZI F-8@NZSP, and 5-ZI F-8@NZSP.

[0033] Example 7

[0034] The prepared composite inorganic solid electrolyte 3-U iO-66@NZSP is mixed with a polymer solid electrolyte and a sodium salt to prepare a solid electrolyte membrane, which specifically includes the following steps:

[0035] First, PVDF-HFP was mixed in a DMF solvent at a mass ratio of 0.05:1. The mixture was vigorously stirred at room temperature for 12 hours, and NaTFS I was added (the mass ratio of NaTFS I to PVDF-HFP was 1:3). Then 3-U iO-66@NZSP powder was added at a relative solution mass ratio of 5%, and vigorously stirred at room temperature for 12 hours. After that, the well-dispersed suspension was poured into a glass mold and dried in a glove box for 24 hours to finally obtain a composite solid electrolyte film. The film thickness is 50-100μm, and a 50μm composite solid electrolyte membrane is preferred in the experiment.

[0036] Example 8

[0037] The prepared composite inorganic solid electrolyte 3-MI L-101(Cr)@NZSP is mixed with a polymer solid electrolyte and a sodium salt to prepare a solid electrolyte membrane, which specifically includes the following steps:

[0038] First, PVDF-HFP was mixed in a DMF solvent at a mass ratio of 0.05:1. The mixture was vigorously stirred at room temperature for 12 hours, and NaTFS I was added at a mass ratio of 3:1 relative to PVDF-HFP. Then 3-MIL-101(Cr)@NZSP powder was added at a relative solution mass ratio of 5%, and vigorously stirred at room temperature for 12 hours. After that, the well-dispersed suspension was poured into a glass mold and dried in a glove box for 24 hours to finally obtain a composite solid electrolyte film. The film thickness is 50-100μm, and a 50μm composite solid electrolyte film is preferred in the experiment.

[0039] Comparative Example 1

[0040] The same as the implementation of Example 1, except that 1-ZIF-8@NZSP was replaced by NZSP solid electrolyte.

[0041] Control group 2:

[0042] The same as the implementation method of Example 7, except that 3-UiO-66@NZSP is replaced by NZSP.

[0043] Control group 3:

[0044] The implementation method is the same as that of Example 1, but the solid electrolyte membrane does not contain a composite inorganic solid electrolyte, but only contains a polymer solid electrolyte and a sodium salt.

[0045] Control group 4:

[0046] The implementation method is the same as that of Example 7, but the solid electrolyte membrane does not contain a composite inorganic solid electrolyte and only contains a polymer solid electrolyte and a sodium salt.

[0047] The solid electrolyte membranes obtained in the above-mentioned Examples 2-8 and Comparative Examples 1-4 were assembled from bottom to top into a positive electrode sheet, a stainless steel sheet, a solid electrolyte membrane, a stainless steel sheet, a spring sheet and a negative electrode sheet to form an all-solid-state battery for ion conductivity testing.

[0048] Ionic conductivity test: According to the calculation formula σ = L / (R·S), where σ is the conductivity (unit S / cm), L is the thickness of the solid electrolyte (unit cm), R is the impedance (unit Ω), and S is the contact area between the stainless steel sheet and the solid electrolyte sheet (unit cm). 2 ) to calculate the ionic conductivity of the electrolyte material. The specific operation method is: assemble a symmetrical cell of blocking electrode | solid electrolyte | blocking electrode, and the selected blocking electrode is a stainless steel sheet. The test is performed in the AC impedance test mode of the electrochemical workstation, and the test parameters are set to 10 6 Hz~10 -2 Hz, amplitude is 15mV. The test results of electrolyte membrane ion conductivity are shown in Table 1.

[0049] Table 1

[0050]

[0051]

[0052] From the above results, it can be seen that in Examples 2-6, the metal organic framework coating layers of different thicknesses are obtained by adjusting the mass ratio of ZIF-8 to the oxide solid electrolyte NZSP. It can be seen that when the mass ratio of the constituent material ZIF-8 of the metal organic framework coating layer to the oxide solid electrolyte is 3:20, the ionic conductivity is the highest, and 8.0 (10 -4 S / cm); at the same time, Examples 7-8 were tested by changing the constituent materials of the metal organic framework coating layer, and all achieved good results.

[0053] The solid electrolyte membrane with the best ionic conductivity test result obtained, that is, Example 4, is tested, including the following steps:

[0054] Preparation of positive electrode sheet: Na3V2(PO4) was used as the positive electrode active material. Na3V2(PO4), PVDF, Super P and NaCl O4 were mixed in N-methylpyrrolidone (NMP) at a mass ratio of 70:18:10:2, and the prepared composite positive electrode slurry was scraped onto aluminum foil and dried in a vacuum oven at 60°C for 12 hours to obtain a positive electrode sheet.

[0055] All-solid-state battery assembly: First, attach metal Na to one side of the solid electrolyte membrane, then attach the prepared positive electrode to the other side of the solid electrolyte membrane, and perform a 50Mpa cold pressing process on the battery to finally obtain an all-solid-state sodium metal battery. The charge and discharge voltage of the battery test is set to 2.5V-3.8V, and the nominal specific capacity is set to 120mAh g -1 , the test temperature is 60℃, the test results are as follows Figure 1 As shown, the capacity retention rate of the all-solid-state battery assembled at 60°C is above 95% after 60 cycles, which has a good capacity retention rate.

[0056] In summary, the technical solution of the present invention forms a metal organic framework coating layer by coating a flexible metal organic framework material (MOFs) with a highly ordered network structure and a deformable skeleton on the surface of the oxide solid electrolyte, which can avoid the degradation of its electrochemical performance due to changing the microstructure of the oxide solid electrolyte or adding other components, forming a composite active material, which is then compounded with a polymer solid electrolyte to improve the ionic conductivity of the electrolyte. The all-solid-state sodium metal battery assembled with it as a solid electrolyte membrane can be stably cycled, and the all-solid-state battery assembled at 60°C with an electrolyte membrane with optimal ionic conductivity has a capacity retention rate of more than 95% after 60 cycles, which has a good capacity retention rate.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A solid electrolyte membrane, characterized in that: It comprises a composite inorganic solid electrolyte, a polymer solid electrolyte and a sodium salt; the composite inorganic solid electrolyte comprises an oxide solid electrolyte and a metal organic skeleton coating layer coated on the surface of the oxide solid electrolyte.

2. The solid electrolyte membrane according to claim 1, characterized in that The oxide solid electrolyte is Na3Zr2Si2PO 12 、Na-β"-Al2O3、NaZr2P3O 12 、Na2Zr2SiP2O 12 、Na4Zr2Si3O 12 The constituent material of the metal organic framework coating layer is one of ZIF-8, 1,4-dicarboxyphenylzirconium, and MIL-101 (Cr).

3. The solid electrolyte membrane according to claim 2, characterized in that The composite inorganic solid electrolyte is prepared by the following method: the constituent material of the metal organic framework coating layer is mixed with the oxide solid electrolyte and then ball milled; Preferably, the mass ratio of the constituent material of the metal organic framework coating layer to the oxide solid electrolyte is (1-5):20; Preferably, the ball milling time is 1-10 h, preferably 5 h; the ball milling speed is 400-600 rpm / min, preferably 500 rpm / min.

4. The solid electrolyte membrane according to claim 1, characterized in that The particle size of the oxide solid electrolyte is 0.5-5 μm; the thickness of the metal organic framework coating layer is 50-800 nm, preferably 300-600 nm; more preferably 400-450 nm.

5. The solid electrolyte membrane according to claim 1, characterized in that The polymer solid electrolyte is (polyvinylidene fluoride-hexafluoropropylene) copolymer PVDF-HFP; the sodium salt is one of sodium perchlorate and bis(sodium trifluorosulfonimide).

6. The solid electrolyte membrane according to claim 1, characterized in that The thickness is 50-100 μm, preferably 50 μm.

7. The solid electrolyte membrane according to claim 1, characterized in that The mass ratio of the composite inorganic solid electrolyte, the polymer solid electrolyte and the sodium salt is: (1-10): (1-10): 1; preferably (3-6): (3-5):

1.

8. A method for preparing the polymer solid electrolyte and sodium salt according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: first, adding a polymer solid electrolyte into a solvent and stirring the mixture, adding a sodium salt and a composite inorganic solid electrolyte, and vigorously stirring the mixture to obtain a well-dispersed suspension; pouring the mixture into a mold to form a film to obtain a solid electrolyte membrane; preferably, the solvent is one or a mixture of DMF, DMAC or acetone.

9. A solid-state battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and the solid electrolyte membrane according to any one of claims 1 to 7.

10. The solid-state battery according to claim 9, characterized in that: The positive electrode sheet uses Na3V2(PO4) as the positive electrode active material; The positive electrode sheet is prepared in the following manner: Na3V2(PO4), PVDF, Super P and NaClO4 are mixed in proportion in N-methylpyrrolidone, the prepared composite positive electrode slurry is scraped on aluminum foil, and then dried; preferably, the mass ratio of Na3V2(PO4), PVDF, Super P and NaClO4 is 70:18:10:2.